IT manager's handbook : getting your new job done - Holtsnider, Bill, 1956-; Jaffe, Brian D. (Elsevier, Morgan Kaufmann, 2012)
"This book provides a practical reference that you will return to again and again in an ever-changing corporate environment where the demands on IT continue to increase. Make your first 100 days really count with the fundamental principles and core concepts critical to your success as a new IT Manager outlined in this valuable resource. The book also discusses how to work with your customers, manage your budget, develop an overall IT strategy and demonstrate the value of IT to the company"--Resumé vydavatele